I think you would put 570 in the blank since 19 x 3 = 57
he must buy 24 jackets to get atheist 260 dollars
Answer:
The product of the expression is -12s² + 11st - 2t²
Step-by-step explanation:
(-3s + 2t)(4s - t)
Use the foil method to multiply the terms. So, we distribute -3s to (4s - t) and we will also distribute 2t to (4s - t) as well.
-12s² + 3st + 8st - 2t²
Now combine like terms.
-12s² + 11st - 2t²
1. x=4+y-2z (move all terms not containing x to the right side of the equation) ; y= -4x + x + 2z (isolate) ; z= 2 - x/2 + y/2 (isolate)
2. y= 1/4x + 17/2 (slope intercept form)
3. x= -32/5 + 3y/5 + 2z ; y=32/3+5x/3-10z/3 ; z= 16/5+x/2 - 3y/10 (isolate the variable by dividing each side by factors that don’t contain variable)
The answer is 1110
step by step explanation: